Regional water balance and slope stability analyses with field measurements - Chew, Jeremy Wei Jie (Nanyang Technological University, 2023)
Climate change has resulted in more erratic and severe rainfall patterns, which increase the likelihood and frequency of slope failures caused by rainfall. This is particularly concerning for tropical countries, such as Singapore, where heavy rain is common. In Singapore, residual soil slopes typically have deep water tables, meaning that rainfall-induced slope failures occur in the unsaturated soil zone. Therefore, it is important to include unsaturated soil mechanics in water balance and slope stability analyses to better identify slopes that are at risk of failure. This study aims to evaluate whether three-dimensional (3D) numerical analysis results generated from GEOtop software is consistent with field measurements recorded by moisture sensors on site in response to rainfall events. Scoops3D software is then used to demonstrate how water balance analysis results can be applied to slope stability analyses. Two slopes were used for regional analyses, one being a slope in Dalvey Road located within the Bukit Timah Granite (BTG) zone while the other is a slope in Bidadari Park Drive located within the Old Alluvium (OA) zone. Regional GEOtop analyses were conducted at both zones before volumetric water content values are extracted for the respective analyses period at the toe and crest of both slopes for different soil layers. Outputs from GEOtop analyses were then used as inputs for Scoops3D analyses to generate the factor of safety (FOS) values. The outcome of this study shows that numerical analysis results were more conservative than the actual field conditions in response to rainfall events. Generally, shallower soil layers experience a more significant increase in volumetric water content in response to rainfall as compared to deeper soil layers because it takes time for water to infiltrate deeper depths of soil. FOS values were consistently observed to drop by the greatest extent after a maximum rainfall event. Pore-water pressure profiles for soils at both zones and both toe and crest positions agree well with the change in FOS values. Despite differences in volumetric water content values generated from regional analyses, the results still proved to be reliable and meaningful. Field measurements are tedious to implement on a regional scale. Therefore, regional analyses serves as a convenient and efficient way to analyse water balance for a large region, whereby the results can then be used for slope stability analyses.